2021
DOI: 10.3390/rs13132601
|View full text |Cite
|
Sign up to set email alerts
|

The Preliminary Study of Dust Devil Tracks in Southern Utopia Planitia, Landing Area of Tianwen-1 Mission

Abstract: China’s first Mars exploration mission (Tianwen-1) landed on the southern part of Mars’ Utopia Planitia on 15 May 2021. The Zhurong rover will focus on high-resolution and in situ observations of key areas on the surface of Mars. Dust devils (DDs) are heat-driven vortices that lift material from the surface and inject it into the atmosphere. The dark or bright surface lineaments left by DDs are called dust devil tracks (DDTs). Dust devils can clear dust from solar panels deposited by gusts and dust storms. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
(68 reference statements)
2
7
0
Order By: Relevance
“…Several cameras and imaging system onboard orbiters have provided DD images from which the size of the DD can be estimated (e.g., Cantor et al., 2006; Cushing et al., 2005; L. Fenton et al., 2016; Fisher et al., 2005; Reiss, Hoekzema, & Stenzel, 2014; Reiss, Spiga, & Erkeling, 2014; Stanzel et al., 2008; Thomas & Gierasch, 1985; Towner, 2009). Orbiters also provide images of the tracks produced by the DDs on the Martian surface (e.g., Cantor et al., 2006; Reiss et al., 2016; Wang et al., 2021; Whelley & Greeley, 2008), allowing the occurrence of these phenomena during a given time period and in specific regions of the planet to be estimated. These measurements, covering large geographic areas, have demonstrated that DDs can be found at a wide range of latitudes (from 0 to about 70° in both hemispheres) and at any longitudes on Mars.…”
Section: Introductionmentioning
confidence: 99%
“…Several cameras and imaging system onboard orbiters have provided DD images from which the size of the DD can be estimated (e.g., Cantor et al., 2006; Cushing et al., 2005; L. Fenton et al., 2016; Fisher et al., 2005; Reiss, Hoekzema, & Stenzel, 2014; Reiss, Spiga, & Erkeling, 2014; Stanzel et al., 2008; Thomas & Gierasch, 1985; Towner, 2009). Orbiters also provide images of the tracks produced by the DDs on the Martian surface (e.g., Cantor et al., 2006; Reiss et al., 2016; Wang et al., 2021; Whelley & Greeley, 2008), allowing the occurrence of these phenomena during a given time period and in specific regions of the planet to be estimated. These measurements, covering large geographic areas, have demonstrated that DDs can be found at a wide range of latitudes (from 0 to about 70° in both hemispheres) and at any longitudes on Mars.…”
Section: Introductionmentioning
confidence: 99%
“…Background wind has a double role, then—low winds allow larger vortices to form, and give them longer to act on a surface. It seems likely that Global Circulation Models may allow the prediction of these factors, but remote sensing of dust devil tracks gives a first‐order prediction of dust lifting: the Chinese Zhurong rover appears to have also succumbed to the Martian environment, likely as a result of dust deposition on its solar arrays, and it is notable that the dust devil tracks at its Utopia landing site are narrow and straight ( S ∼ 1.01, e.g., Wang et al., 2021), just like at Elysium, suggesting a priori that cleaning events would be infrequent at best. Beware pinstripes!…”
Section: Figurementioning
confidence: 99%
“…In addition, the temporal and spatial probabilities of dust storm activity in southern Utopia Planitia ranges from 0% to 14.13% and 0% to 11.87%, respectively, during the EDL season of the Tianwen-1 mission [20,21]. Dust devil track (DDT) formation rates in the Tianwen-1 landing area were computed and analyzed within the range of 0.00006 to 0.1275 ddt km −2 sol −1 , mainly affected by factors such as the season and dust storm occurrence [22]. The spatial aggregation of three Martian surface temperature indicators, including sol average temperature, sol temperature range, and sol-to-sol temperature change, were quantitatively evaluated using clustering analysis at the global scale and in the Tianwen-1 landing area [23,24].…”
Section: Dust Storm Morphology and Classificationmentioning
confidence: 99%